Tax Avoidance Moderates The Determinants Of Firm Value (Study On Construction Companies In Indonesia) - Aprilia Eka Tristanto; Dwi Suhartini (Jurnal Ekonomi, 2024)
The purpose of the study was to examine the effect of profitability, leverage, and liquidty on firm value with tax avoidance as a moderating variabel. Measurement of firm value is carried out using Price book Value (PBV). Meanwhile, profitability uses Return On Assets (ROA), leverage uses Debt Equity Ratio (DER), liquidity uses Current Ratio (CR), and tax avoidance uses Cash Effective Tax Ratio (CETR).  The population used in this study are construction companies listed on Indonesia Stock Exchange for the period 2017-2022. The sample used are 9 companies using the purposive sampling method. The type of data used is secodary data and the analyze method used is Moderated Regression Analysis (MRA) using SPSS 22. The result of this study obtained that profitability has positive and significant effect on firm value,  while leverage and liquidty have no effect on firm value. As moderating variabel, tax avoidance cannot moderate the effect of profitability, leverage, and liquidity on firm value.